Formulasi Food Bar Sebagai Snack Bagi Penderita Diabetes Mellitus Berbahan Ubi Jalar Ungu (Ipomoea Batatas L. Poir) Dan Kacang Merah (Phaseolus Vulgaris L.) Pratanak Dilihat Dari Kadar Amilosa Dan Gula Reduksi - Carella, Hilda, Fitriana Mustikaningrum, S.Gz, M.Sc, Rusdin Rauf, S.TP., M.P (2016)
Introduction:Snacks appropriate for diabetics is needed to control blood sugar level. mellitus is absolutely necessary in order to control blood glucose levels. Purple sweet potato and red bean parboiled can be used as raw materials for making food bar that produces a low blood sugar. Objective: To determine the formulation of the food bar made from purple sweet potato and red bean parboiled by reducing sugar and amylose. Methods: The study design used a completely randomized design with three (3) treatment of the different formulations of purple sweet potato and red bean with a ratio of 90%: 10%; 80%: 20%; 70%: 30%. Reducing sugar using the Nelson-Somogyi and amylose by spectrophotometer method. Data analysis and amylose reducing sugar using one way ANOVA test, if there are differences continued test of Duncan with a 95% confidence level. Results: reducing sugar and high amylose in food formulations bar 90%: 10% at 12.58% and 9.33%, while reducing sugar and low amylose in food formulationsbar 70%: 30% at 9.68% and 7,10%. Conclusion: There is the influence the formulation of food bars made from purple sweet potato and red bean parboiled towards reducing sugar and amylose. Suggestion: Making food bar using a composition ratio of purple sweet potato flour and red beans parboiled by 90%: 10% as it has the highest amylose content.